Stability of microencapsulated mangosteen pericarp anthocyanin as a natural food colorant: a kinetic study - Deylami, Mahsa Ziabakhsh; Abdul Rahman, Russly; Bakar, Jamilah; Tan, Chin Ping; Olusegun, Lasekan (Faculty of Engineering, Universiti Putra Malaysia, 2016)
The increasing consumer preference for natural products has resulted in growing the functional and natural food market in which natural colors are highly demanded. Anthocyanins are interesting natural red colorants. Mangosteen pericarp is a promising source of natural color because it is agriculture waste and rich in anthocyanins. Anthocyanins are intrinsically susceptible to adverse conditions of environment and microencapsulation is a well-known process to improve their stability. Mangosteen pericarp was microencapsulated using spray-drying technique with maltodextrin (DE 10) as encapsulant. Microencapsulation efficiency of 95.7% was obtained for anthocyanins. Thermal stability of microencapsulated anthocyanins in reconstituted form was studied over the temperature range of 75-95°C for 30 min. The result was fitted to Weibull, first-order and zero-order kinetic models. Weibull kinetic model had higher correlation coefficients and lower values of standard error of mean, therefore, most accurately predicted anthocyanin degradation. Kinetics parameters showed anthocyanin degradation was strongly dependent on the temperature. The activation energy was 32.45 kJ/mol. Microencapsulated mangosteen pericarp can potentially be used as an anthocyanin-based natural red colorant in food industry under mild process conditions.